Zur Evolution der fundatrigenen und virginogenen Anholozyklie im Adelgidae-Genus Sacchiphantes Curtis 1844 (Hemiptera: Aphidoidea). - Steffan, August Wilhelm (Contributions to Entomology = Beiträge zur Entomologie, 1961)
The above publication deals with the problem of evolution of the anholocyclic-parthenogenetic life cycles in the genus Sacchiphantes Curtis 1844. The fundatrigen-monoecic anholocycle on Picea abies - S. abietis (Linnaeus 1758) - as well as the virginogen-monoecic anholocycle on Larix decidua - S. segregis Steffan 1961 - prove to be independent species. They do not have any cyclic connection with the heterogenetic-dioecic holocycle - S. viridis (Ratzeburg 1843), but they are derived from this species phylogenetically, and they are members of the same superspecies.